Deforestation risk due to commodity crop expansion in sub-Saharan Africa. (4th April 2017) - Ordway, Elsa M; Asner, Gregory P; Lambin, Eric F
Abstract: Rapid integration of global agricultural markets and subsequent cropland displacement in recent decades increased large-scale tropical deforestation in South America and Southeast Asia. Growing land scarcity and more stringent land use regulations in these regions could incentivize the offshoring of export-oriented commodity crops to sub-Saharan Africa (SSA). We assess the effects of domestic- and export-oriented agricultural expansion on deforestation in SSA in recent decades. Analyses were conducted at the global, regional and local scales. We found that commodity crops are expanding in SSA, increasing pressure on tropical forests. Four Congo Basin countries, Sierra Leone, Liberia, and Côte d'Ivoire were most at risk in terms of exposure, vulnerability and pressures from agricultural expansion. These countries averaged the highest percent forest cover (58% ± 17.93) and lowest proportions of potentially available cropland outside forest areas (1% ± 0.89). Foreign investment in these countries was concentrated in oil palm production (81%), with a median investment area of 41 582 thousand ha. Cocoa, the fastest expanding export-oriented crop across SSA, accounted for 57% of global expansion in 2000–2013 at a rate of 132 thousand ha yr −1 . However, cocoa only amounted to 0.89% of foreign land investment. Commodity crop expansion in SSA appears largely driven by small- and medium-scale farmers rather than industrial plantations. Land-use changes associated with large-scale investments remain to be observed in many countries. Although domestic demand for commodity crops was associated with most agricultural expansion, we provide evidence of a growing influence of distant markets on land-use change in SSA.